Patient classification systems in nursing - Lemonidou, Chryssoula; Merkouris, Anastasios (My University, 1996)
In a health care environment with continuously increasing patient needs and economic constraints, nurse executives concern about the quality, cost and effectiveness of the health services. There is a need for better use of the available, and usually scarce resources, as well as for documentation of the extent to which these resources contribute to the patient outcomes. Patient classification systems (PCSs) were developed in the 1960s for staffing purposes. Today, PCSs are a valuable tool not only for allocating staff, but also for supporting cost services, QA/QI programs, measurement of patient outcomes, research and decision making. This paper intends to give a brief description and discuss the use, the problems, the strategies which are implemented as a response to these problems and the future directions of the PCSs.